2023
DOI: 10.18632/aging.205254
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced serum levels of tumor necrosis factor-α, interleukin-1β, and -6 in sarcopenia: alleviation through exercise and nutrition intervention

Ke-Vin Chang,
Wei-Ting Wu,
Yu-Hsin Chen
et al.

Abstract: Background: Limited research has been conducted on the post-intervention inflammatory status in sarcopenic patients, despite previous studies revealing elevated pro-inflammatory markers. This study aimed to investigate the potential elevation of specific pro-inflammatory cytokines in sarcopenic patients and evaluate the effects of exercise and nutritional support interventions on these cytokine levels. Methods: In this post-hoc analysis of a randomized controlled trial (RCT), 57 individuals with sar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Circulating cytokine level modulation using diet interventions has been suggested in different clinical scenarios; for example, some studies have reported decreased IL-6 levels after the consumption of low-calorie diet, berry, whole wheat and polyunsaturated fatty acids in patients with metabolic syndrome [ 47 ], decreased IL-6 levels after supplementation with branched-chain amino acids, calcium and vitamin D3 in patients with elderly sarcopenia [ 48 ], or decreased IL-18 levels after Mediterranean diet and supplementation with very long chain omega-3 polyunsaturated fatty acid in men with high-risk of atherosclerosis (despite mild changes in body composition parameters) [ 49 ]. In contrast, in this study we did not observe significant changes in circulating cytokine levels after three months of nutritional support; far from considering this fact as a treatment failure, it represents a positive clinical response to nutritional treatment, since all patients were receiving systemic treatment during the study period, and despite this, circulating cytokine levels did not increase, as could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating cytokine level modulation using diet interventions has been suggested in different clinical scenarios; for example, some studies have reported decreased IL-6 levels after the consumption of low-calorie diet, berry, whole wheat and polyunsaturated fatty acids in patients with metabolic syndrome [ 47 ], decreased IL-6 levels after supplementation with branched-chain amino acids, calcium and vitamin D3 in patients with elderly sarcopenia [ 48 ], or decreased IL-18 levels after Mediterranean diet and supplementation with very long chain omega-3 polyunsaturated fatty acid in men with high-risk of atherosclerosis (despite mild changes in body composition parameters) [ 49 ]. In contrast, in this study we did not observe significant changes in circulating cytokine levels after three months of nutritional support; far from considering this fact as a treatment failure, it represents a positive clinical response to nutritional treatment, since all patients were receiving systemic treatment during the study period, and despite this, circulating cytokine levels did not increase, as could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of IL-6, IL-1β, TNF-α, and CRP have been identified as potential contributors to the unfavorable outcomes of sarcopenia in PD-1 inhibitor treatment. Previous studies have demonstrated that sarcopenic patients exhibit higher levels of TNF-α, IL-1β, IL-6, and CRP ( Lee et al, 2007 ; Koshikawa et al, 2020 ; Pan et al, 2021 ; Shokri-Mashhadi et al, 2021 ; Chang et al, 2023 ). IL-6 is primarily produced by monocytes-macrophages, T helper 2 cells (TH2), and other cells, and it plays a role in the differentiation of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-associated muscle wasting is a complex pathological condition involving numerous organs. However, a large number of early studies on cancer-associated muscle wasting focused on circulating inflammation mediators and muscle tissue [6,7].…”
Section: Introductionmentioning
confidence: 99%